Reorientasi Peran Frontline Supervisor: Pelatihan Kepemimpinan untuk Penguatan Disiplin Kerja di PT Kayaba Indonesia - Rut Gloria Anugrah; Langga Lagandhy (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This community service program was conducted at PT Kayaba Indonesia to address disciplinary problems among production operators, including tardiness, non-compliance with personal protective equipment use, and violations of break-time rules. The program aimed to strengthen the capacity of frontline supervisors to manage team discipline through an educative-participatory approach based on contextual leadership training. Activities included needs identification, material development, interactive classroom training, an initial diagnosis of leadership styles, and evaluation through observation and reflective discussion, involving 50 production supervisors. Results showed that most participants tended toward a transactional leadership style, while disciplinary enforcement remained reactive and target-oriented. The program raised participants' awareness of their strategic role in shaping subordinates' work behavior. These findings point to the need for follow-up actions, including ongoing coaching, integration into the performance management system, and the development of employee communication mechanisms, so that discipline enforcement becomes a consistent and sustainable part of the organizational system.